The Relationship Between Religious Attitudes and the Discipline of Elementary School Students - Rachmawati, Intan; Rosyidi, Muhib (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to examine whether or not there is a relationship between religiosity and the discipline of elementary school students in grade 3 SDN Tengah 01 Pagi, Kramat Jati, East Jakarta. This research falls under the category of quantitative research using the Correlational research method. The population under investigation consisted of 60 third-grade students (III A and III B) of the school. The sampling technique utilized in this study was cluster random sampling, involving a sample size of 56 respondents. As for the primary data sources in the research, they encompass the school principal, teachers, and students. Meanwhile, the secondary data sources are derived from journal articles, books, and other relevant sources related to the research. Data collection methods in this research included questionnaires and observations. Based on the research results, it indicates a strong correlation between religious attitudes and student discipline. The correlation value of 0.623 is positive and has a significance value of 0.001 < 0.05. Thus, there is a positive relationship or correlation between religious attitudes and the discipline of third-grade students of classes III A and III B at SDN Tengah 01 Pagi, Kramat Jati, East Jakarta.